Mass diffusion from a point source in a turbulent boundary layer over a rough surface - Bhaduri, Sachindranarayan, author; Cermak, J. E. (Jack E.), author; Colorado State University, publisher (Colorado State University. Libraries, 1966)
Turbulent diffusion of dynamically passive and chemically nonreactive matter from a simulated point source within a two-dimensional boundary-layer flow over a rough surface was studied. A rough surface consisting of two-dimensional roughness elements (wooden strips, 0.25 in. high, 0.25 in. wide, and 6.0 ft. long, placed 3.0 in. apart normal to the flow direction) was used with the source at three different heights. The free-stream velocity of air for most of the runs was 12.50 ft./sec. Concentrations of the diffusing plume were measured at several downstream distances from the point source located at heights of 0.0625 in., 0.5 in., and 1.0 in. above the rough surface. Anhydrous ammonia was used as the tracer gas. Both vertical and lateral concentration profiles were found to be self- similar in the fully developed regions of the concentration field. The concentration distribution for such regions is described by two dimensionless universal functions, one for the case of source height h = 0.0625 in. and the other for the cases of source heights h = 0.5 in. and h = 1.0 in. These are obtained by expressing the relative concentration C/Cmax in terms of position length parameters n and o- diffusing plume as length scales. The vertical and lateral length scales (n, and o- respectively) of the plume have been related to the downstream distance from the source by empirical equations valid within the range of the experimental variables. The Lagrangian similarity hypothesis was tested by means of the experimental data and found to agree reasonably well with the data for the attenuation of maximum ground-level concentration in the longitudinal direction. Experimental results for the growth of the plume height and width with downstream distance from the source are in fair agreement with predictions of the hypothesis. However, in view of the experimental data, further investigations are necessary for a conclusive test of the hypothesis which seems to afford a rational basis for describing the gross characteristics of the diffusing plume within a turbulent boundary layer.
CER66-67JEC-SB25.
September 1966.
Keywords: Diffusion; Atmospheric turbulence; Boundary layer